PENERAPAN MODEL PREDICT OBSERVE EXPLAIN BERBANTUAN MEDIA SCRAPBOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD - Linda Ayu Kusumaningsih; Fina Fakhriyah; Mila Roysa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to describe the increase in critical thinking skills using the predict observe explain learning model assisted by scrapbook media in class V SD 1 Jepang Kudus. This type of research is classroom action research. This type of research is classroom action research. This research consists of 4 stages namely planning, action, observation, and reflection. The research was conducted in 2 cycles with 2 meetings each cycle. The subjects of this study were 27 students of grade V SD 1 Jepang Kudus in the 2019/2020 school year. The results showed that students' critical thinking skills in cycle 1 obtained classical completeness by 63% with the criteria needed guidance, while in cycle 2 they obtained classical completeness by 85% with good criteria.